Manajemen Perpustakaan SD Marsudirini Surakarta - Triyono, Agustinus, Dr.Suyatmini,SE.,M.Si, Dr. Maryadi, M.A (2017)
This study aimed to 1)describe the elementary school library planning Marsudirini Surakarta, 2)organizing library Marsudirini Surakarta Elementary School, 3)Elementary School library Marsudirini leadership and 4)supervision and assessment Surakarta Elementary School library Marsudirini Surakarta. This study is a qualitative research with this type of ethnographic research. Data collection technique used interview, observation and documentation, with analysis of the data includes, data reduction, data presentation and conclusion. Planning begins with the library planned destination library, the library planning procedures, budget planning and financial planning libraries and library book collection. In organizing the library, starting with forming the organizational structure of the library, the establishment of library work program in order to achieve common goals and the establishment of the discipline of the school library. The results of the research library leadership necessary education, training and experience to the library manager. Supervision libraries and assessment is carried out directly by the principal, surveillance was conducted on the funding of libraries, procurement of books of fiction and non-fiction, the procurement for the library, the state of the facilities and infrastructure of the library, state library's collection of materials, library work program and procedures of the library. Keywords: management, school library, library management